Physical properties of high-temperature superconductors - Wesche, Rainer, 1956- (Wiley series in materials for electronic and optoelectronic applications, 2015)
This book provides an overview of materials aspects of high-temperature superconductors, combining introductory aspects, description of new physics, material aspects and a description of the material properties. This title is suitable for researchers in materials science, physics and engineering and also for technicians interested in the applications of superconductors.